Sharenting Ethics in Indonesian Family Communication Through Cultural Values of Digital Parenting - Frasetya, Vito (Al Huwiyah: Journal of Woman and Children Studies, 2024)
This research examines the phenomenon of sharenting (sharing-parenting) in the Indonesian cultural context, focusing on how traditional values influence digital parenting practices. This research uses a comprehensive literature study methodology to analyse the intersection between local wisdom and digital communication ethics in care. This study reveals that Indonesian parents practice sharenting through three main cultural pillars: harmony, unggah ungguh, and tepo seliro. These values significantly shape how information about children is shared on social media, creating patterns that differ from Western individualistic approaches. The findings show that parenting practices in Indonesia's digital era are firmly rooted in collective cultural values, where sharing information about children is not simply seen as personal documentation but as part of communal responsibility. This research identifies unique challenges in balancing traditional values with digital privacy concerns, especially in how Indonesian parents interpret and implement privacy boundaries within their collective cultural framework. This study contributes to developing a culturally sensitive ethical framework for digital parenting in Indonesia, emphasizing a balance between traditional values and modern digital practices. Findings suggest practical sharing guidelines in Indonesia must integrate collective cultural values while addressing contemporary digital privacy concerns. Furthermore, this research proposes practical recommendations for implementing culturally appropriate digital literacy programs and developing policies that protect children's interests while respecting traditional family values.